FORUM: Effective management of ecological resilience – are we there yet?. Issue 5 (31st July 2015) - Spears, Bryan M.; Ives, Stephen C.; Angeler, David G.; Allen, Craig R.; Birk, Sebastian; Carvalho, Laurence; Cavers, Stephen; Daunt, Francis; Morton, R. Daniel; Pocock, Michael J. O.; Rhodes, Glenn; Thackeray, Stephen J.
Summary: Ecological resilience is developing into a credible paradigm for policy development and environmental management for preserving natural capital in a rapidly changing world. However, resilience emerges from complex interactions, limiting the translation of theory into practice. Main limitations include the following: (i) difficulty in quantification and detection of changes in ecological resilience, (ii) a lack of empirical evidence to support preventative or proactive management and (iii) difficulties in managing processes operating across socio‐ecological systems that vary in space and time. We highlight recent research with the potential to address these limitations including new and/or improved indicators of resilience and tools to assess scale as a driver of resilience. Synthesis and applications . Effective resilience‐based management must be adaptive in nature. To support this, we propose an operational model using resilience‐based iterative management actions operating across scales. Abstract : Effective resilience‐based management must be adaptive in nature. To support this, we propose an operational model using resilience‐based iterative management actions operating across scales.